Reactive lymphoid hyperplasia of the thyroid followed by systemic autoimmune diseases: a case report - Onoda, Naoyoshi (BioMed Central, 2014)
INTRODUCTION: Reactive lymphoid hyperplasia is a benign nodular lesion characterized by marked proliferation of non-neoplastic, polyclonal lymphocytes forming follicles. The lesion is found in various organs such as skin, orbit, lung, gastrointestinal tract, and liver. However, reactive lymphoid hyperplasia in the thyroid gland is extremely rare. Here, we present an interesting case of reactive lymphoid hyperplasia in the thyroid, which suggests the nature of the disease. CASE PRESENTATION: A 74-year-old Japanese man was referred to our institute because of a growing well-demarcated irregular-shaped mass in the right lobe of the thyroid. Malignant lymphoma was suspected by cytology, and right lobectomy was conducted. A final diagnosis of reactive lymphoid hyperplasia was made by the intimate investigation of the surgical specimen, with evidence of polyclonal and non-neoplastic lymphatic proliferations forming follicles with an active germinal center. After an initial uneventful postoperative course, our patient developed severe symptoms of systemic rheumatic arthritis, and alterations in autoimmune reaction, including clinically overt chronic thyroiditis, were identified. CONCLUSIONS: Our case demonstrated important clinical information on reactive lymphoid hyperplasia of the thyroid, and suggested the importance of differential diagnosis, and possible close correlation between systemic autoimmune disorder and the disease.